Associations between adverse childhood experiences and health service utilisation, prescription claims, and school performance during adolescence - Wijekulasuriya, Shalini; Lystad, Reidar; Zurynski, Yvonne; Harrison, Reema; Braithwaite, Jeffrey; Mitchell, Rebecca (My University, 2025)
Adverse childhood experiences (ACEs) can affect childhood development, often leading to detrimental outcomes in adolescence and adulthood. This study examined the characteristics of young people who experience ACEs, and the association between ACEs in childhood and health service use, prescription claims, and educational achievement in adolescence. This study utilised the Longitudinal Study of Australian Children (LSAC) Kindergarten Cohort, with biennial surveys from age 4 regarding health, social, and family domains. ACEs exposure during childhood (4-11 years) were centred on household dysfunction, including parental separation, parental substance abuse, parental mental illness, or domestic violence. LSAC survey data was linked to administrative health service and education data, which were used to determine number of health service claims, prescription claims, health service costs, and poor educational achievement during adolescence (12-19 years). Around 62% of the cohort experienced ≥1 ACE during childhood. Young people experiencing ACEs had higher odds of poor mental health and lower odds of a physical health condition in adolescence, however, ACEs were not associated with total health service claims, total prescription claims, or total health service costs in the same period. Exposure to one ACE compared to no ACEs resulted in higher odds of poor numeracy in Grade 7, and poor numeracy and poor reading achievement in Grade 9. There was inconsistent evidence of a dose-response relationship between ACEs and poor educational achievement. In this study, the association between ACEs and educational achievement, but not health service outcomes in adolescence may be due to accessibility factors. Future interventions could integrate health and social care services to better support families affected by ACEs.
Keywords: Academic achievement; Adolescence; Adverse childhood experiences; Development; Health service use; Adolescents and youth; Disadvantage, adversity and resilience; Childhood and child development; Health and wellbeing; Intergenerational transfer; Learning, education and training